Determinants of Birth Asphyxia among Newborn in a Zonal Hospital - Rijal, Mala; Chaudhary, Tanuja Kumari; Saha, Abhilasha (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: Birth asphyxia is a leading cause of brain damage. Early identification and managing of its contributing factor would change the burden of birth asphyxia. Therefore, the objective of this study was to identify the determinants of birth asphyxia among newborn in a zonal hospital, Dhanusha, Nepal. Material and Methods: A case control study was carried out among 192 newborns where cases and controls were taken in the ratio of 1:1. Newborns with an APGAR score of less than 7 at 1 min and 5 min were taken as cases, and those with greater or equal to 7 were taken as controls. Case includes all asphyxiated newborns at time of data collection. There were total 96 birth asphyxiated newborn and equal number of non-asphyxiated newborn meeting the inclusion criteria were included as a control group. Data was collected by using structured interview schedule and chart review. The data was entered into SPSS version 16. The data were analyzed by frequency, percentage, mean, standard deviation, chi-square test and odd ratio. Those variables with a p-value <0.05 were identified as significant determinants of birth asphyxia. Results: Findings revealed that rural residency (79.2%), dalit ethnicity (69.6%) and joint family (92.7%) were socio-demographic determinants of birth asphyxia. Finding also revealed that primi-parity (OR:3.2,95%CI:1.7-8.2),problem during pregnancy(OR:3.1,95%CI:1.5-6.6), premature rupture of membrane (OR:23.4, 95%CI: 8.7-62.7), augmentation of labour with oxytocin (OR:12.3, 95%CI:6.1-24.4), sex of newborn (OR:5.0, 95%CI;2.7-9.4), meconium stained amniotic fluid (OR:0.22,95%CI:0.00-0.05), cord round the neck (OR:19.0,95%CI:2.4-24.6) and height of mother (OR:16.2,95% CI:2.0-126.0) were significantly associated with increase odds of birth asphyxia. Conclusion: Most of the identified determinants were common and familiar causes of birth asphyxia. Early detection can prevent and control birth asphyxia. Thus, every pregnant woman need for better maternal care, so creating awareness about determining factors of birth asphyxia to the midwives, careful monitoring of labour, and identifying and taking proper measures that would help in decreasing the occurrence of birth asphyxia.